The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1996
DOI: 10.1016/0735-1097(96)00091-5
|View full text |Cite
|
Sign up to set email alerts
|

Influence of cigarette smoking on rate of reopening of the infarct-related coronary artery after myocardial infarction: A multivariate analysis

Abstract: These observational data, if replicated, suggest that in patients with acute myocardial infarction, thrombolytic therapy may be most effective in current smokers, whereas nonsmokers and ex-smokers may require other management strategies, such as emergency percutaneous transluminal coronary angioplasty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(22 citation statements)
references
References 28 publications
3
19
0
Order By: Relevance
“…Actually, this finding is consistent with the data in literature (20)(21)(22). Smoking is associated with a hypercoagulable state, particularly higher fibrinogen, compared to non-smokers (23).…”
Section: Discussionsupporting
confidence: 93%
“…Actually, this finding is consistent with the data in literature (20)(21)(22). Smoking is associated with a hypercoagulable state, particularly higher fibrinogen, compared to non-smokers (23).…”
Section: Discussionsupporting
confidence: 93%
“…19 Indeed, it has been provocatively suggested that thrombolytic therapy should be given only to smokers and that such alternative strategies as primary angioplasty be used in nonsmokers. 20 Our findings may account for these observations, because it might be anticipated that patients with impaired coronary endothelial cell tPA release would benefit most from thrombolytic therapy.…”
Section: Discussionmentioning
confidence: 59%
“…87 This may, in part, be explained by the finding that in current smokers the infarct related artery is more likely to become patent after thrombolytic therapy. 87 These observations are consistent with these findings on endothelial t-PA release because it might be anticipated that patients with impaired endothelial cell t-PA release would benefit most from thrombolytic therapy, whereas those with a normal endogenous fibrinolytic capacity are more likely to have coronary thrombus resistant to fibrinolysis.…”
Section: Smokingmentioning
confidence: 94%
“…Alternatively, hypertension and smoking may have different effects Figure 4. After myocardial infarction, smokers have a lower in-hospital mortality than nonsmokers (A) (data from Barbash et al 100 ), possibly because thrombolytic therapy is more effective in smokers (B) (data from de Chillou et al 87 ). Differences in the capacity for acute t-PA release in the coronary circulation (C) (data from Newby et al 53 ) may explain this observation.…”
Section: Hypertensionmentioning
confidence: 99%
See 1 more Smart Citation